Evaluation of MMP-10 and TIMP-1 levels associated with Resveratrol supplementation. (24th June 2020) - Silva, AM; Ferreira, C; Silva, I; Clemente, M; Figueiredo, JP; Pereira, T; Gabriel, A; Caseiro, A
Abstract: Introduction Resveratrol (RSV) is a natural phytoalexin present in abundance in grapes, berries, peanuts and red wine. The main benefits of resveratrol ingestion are due to its anti-inflammatory and antioxidant properties. This compound also induces therapeutic benefits in the remodelling of extracellular matrix (ECM), which plays an important role in the regulation of the activity of matrix metalloproteinases (MMPs) and its tissue inhibitors of metalloproteinases (TIMPs). The MMPs are a family of zinc dependent endopeptidases, with an important role in the physiological and pathological remodelling of ECM, once the activity of MMPs can be regulated by TIMPs. This regulation is essential, since if there is an imbalance between the MMPs and TIMPs there's destruction of the ECM, leading to the development of several pathologies. Objectives Evaluate RSV potential by determining serum and salivary levels of MMP-10 and TIMP-1. Methodology The study population included 27 undergraduates between the ages of 18 and 30, divided into a control group (placebo) and an intervention group, supplemented with 100 mg RSV/day, during 30 days. MMP-10 and TIMP-1 levels were determined by slot blot. The results were analysed using a GraphPad Prism version 5 software for Windows (GraphPad Software, San Diego, California, USA). Results It was verified the existence of a linear correlation between the serum and salivary levels of TIMP-1, as well as a tendency of increase of this biomarker after RSV supplementation. In all indicators studied, supplementation with this compound wasn't harmful. Conclusion The rising trend verified at TIMP-1 in both fluids may reflect benefits in the individuals under study, demonstrating that saliva has potential as a study biofluid for this type of biochemical markers. It was also verified that supplementation with this compound did not damage the evaluated parameters and, therefore, the RSV potential shouldn't be rejected.